1991
DOI: 10.1038/bjc.1991.146
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new tumour marker CA 242 with CA 19-9, CA 50 and carcinoembryonic antigen (CEA) in digestive tract diseases

Abstract: The levels of CA 242, a new tumour marker of carbohydrate nature, were measured in sera of 185 patients with malignancies of the digestive tract and of 123 patients with benign digestive tract diseases. High percentages of elevated CA 242 levels (greater than 20 U ml-1) were recorded in patients with pancreatic and biliary cancers (68%). The sensitivity was somewhat lower than that of CA 19-9 (76%) and CA 50 (73%). On the other hand, in benign pancreatic and biliary tract diseases the CA 242 level was less fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
44
0
4

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 18 publications
8
44
0
4
Order By: Relevance
“…The CEA test and CA 50 test performed equally well at high and low specificity levels (Figure 1). This analysis shows that the CA 242 test has a clear advantage over CEA and CA 50 because of its higher specificity, confirming thus the results of previous studies (Haglund et al, 1989;Kuusela et al, 1991;Nilsson et al, 1992;Pasanen et al, 1992).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The CEA test and CA 50 test performed equally well at high and low specificity levels (Figure 1). This analysis shows that the CA 242 test has a clear advantage over CEA and CA 50 because of its higher specificity, confirming thus the results of previous studies (Haglund et al, 1989;Kuusela et al, 1991;Nilsson et al, 1992;Pasanen et al, 1992).…”
Section: Discussionsupporting
confidence: 81%
“…Serum CEA and CA 50 are among the most intensively studied tumour markers and their role as reference markers is established (Kalser et al, 1978;Hansen et al, 1974;Lindholm et al, 1983;Jalanko et al, 1985;Masson et al, 1990;Haglund et al, 1992). CA 242 is a novel tumour marker which has proved promising because of its high specificity (Haglund et al, 1989;Kuusela et al, 1991;Nilsson et al, 1992;Pasanen et al, 1992). Evaluation of these marker studies is often difficult because of variance and heterogenity of the reference populations, and perhaps this is one reason why the role of these markers in pancreatic cancer is not yet clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that CA 242 is involved in tumor invasion and metastasis in case of gastric, pancreatic and colorectal cancer, high CA 242 is associated with poor prognosis (Kuusela et al, 1991;Bünger et al, 2011;Rana et al, 2012). To date, however, there have been few studies regarding CA 242 in EC mainly because of its low sensitivity and specificity, resulting in low detection rates and unacceptable false-positive diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…When used in combination with CEA, CA-19-9 (Quentmeier et al, 1987) and (Sagar et al, 1991;Ruggeri et al, 1993) have been shown to provide a gain of positivity in colorectal cancer. The recent studies of showed that it has a higher sensitivity than CA-50 in primary colorectal cancer and a low false positivity in benign liver disease (Kuusela et al, 1991;Nilsson et al, 1992). In prinary colorectal cancer, additional use of CA-242 improves the diagnostic sensitivity of CEA alone (though it still remains limited) (Roberts et al, 1992), and CA-242 has also been shown to compklment CEA monitoring of patients reiing chemotherapy for liver metasta from colorectal cancer (Ward et al, 1993 …”
mentioning
confidence: 99%
“…It is evident that while CEA monitoring during the followup of patients after potentially curative surgery is valuable it lacks the sensitivity and specificity to be an infallible guide to the patient's status (Northover, 1986 (Holmgren et al, 1984), CA-19-9 (Del Villano et al, 1983), (Barghava et al, 1987) and CA-242 (Nilsson et al, 1992), all of which have been shown to be valuable in pancreatic cancer (Kuusela et al, 1991;Taylor et al, 1992;Pasanen et al, 1993) and have been suggested as markers in colorectal cancer. When used in combination with CEA, CA-19-9 (Quentmeier et al, 1987) and (Sagar et al, 1991;Ruggeri et al, 1993) have been shown to provide a gain of positivity in colorectal cancer.…”
mentioning
confidence: 99%